Preparation of Cassava Bagasse Starch-Based Biodegradable Film Reinforced with Chicken Feet Gelatin, Citric Acid as Crosslinker, and Glycerol as Plasticizer - Silviana Silviana; Piontek Benedictus Brandon; Bella Ayu Silawanda (Universitas Gadjah Mada, 2018)
Chicken feet is one of sources used to produce biodegradable films due to inexpensive and abundant source. Chicken feet contains extracted gelatin amount of 27.61 to 33%. This biofilm was prepared from cassava bagasse starch with citric acid as cross-linker and glycerol as plasticizer. Cassava bagasse contains about 40–64% of starch. This paper observes the optimum composition of cassava bagasse starch-based biofilm preparation upon Central Composite Design with variables of gelatin, glycerol, and citric acid concentration with response of tensile strength and elongation at break. This research was executed in several steps, i.e. extraction of gelatin, extraction of cassava bagasse starch, and casting. Optimum condition of this biofilm preparation can be obtained at 12.98% w of gelatin content, 0.22% w of glycerol and 0.27% w of citric acid by releasing 21.73 MPa of tensile strength and 19.73% of elongation at break. Mass loss of biofilm with lower gelatin content gave almost the same mass loss for blank biofilm (cassava bagasse starch-based without gelatin content). Increasing of gelatin content in the biofilm, increasing of the biofilm mass loss. However, the biofilm had good thermal stability by thermal gravimetric analysis with higher temperature to obtain inorganic residue than that of blank biofilm.